Measurement and evaluation practices of factors that contribute to effective health promotion collaboration functioning: A scoping review. (April 2017) - Stolp, Sean; Bottorff, Joan L.; Seaton, Cherisse L.; Jones-Bricker, Margaret; Oliffe, John L.; Johnson, Steven T.; Errey, Sally; Medhurst, Kerensa; Lamont, Sonia
Highlights: Six factors were significantly associated with outcome measures across studies. Leadership was the most studied factor but conceptualizations differed across studies. Drawing conclusions about factor impact on collaboration remains difficult. The use of standardized tools would greatly benefit health promotion collaborations. Abstract: The purpose of this scoping review was to identify promising factors that underpin effective health promotion collaborations, measurement approaches, and evaluation practices. Measurement approaches and evaluation practices employed in 14 English-language articles published between January 2001 and October 2015 were considered. Data extraction included research design, health focus of the collaboration, factors being evaluated, how factors were conceptualized and measured, and outcome measures. Studies were methodologically diverse employing either quantitative methods (n = 9), mixed methods (n = 4), or qualitative methods (n = 1). In total, these 14 studies examined 113 factors, 88 of which were only measured once. Leadership was the most commonly studied factor but was conceptualized differently across studies. Six factors were significantly associated with outcome measures across studies; leadership (n = 3), gender (n = 2), trust (n = 2), length of the collaboration (n = 2), budget (n = 2) and changes in organizational model (n = 2). Since factors were often conceptualized differently, drawing conclusions about their impact on collaborative functioning remains difficult. The use of reliable and validated tools would strengthen evaluation of health promotion collaborations and would support and enhance the effectiveness of collaboration.